Correlation between Body Image and Depression in Pregnant Women - Zafar, Faryal; Hanan, Saima; Sohail, Sumbul; Hussain, Varisha; Nayab (Indus Journal of Bioscience Research, 2025)
Introduction: Pregnancy-related body image dissatisfaction is linked to psychiatric conditions like depression. This study examines the relationship between depression and body image in pregnant women and emphasizes the importance of taking mental health into account throughout pregnancy. Objectives: The purpose of the study was to establish the correlation between body image and depression in pregnant women. Materials and Methods: This cross-sectional study was conducted in Dr Ziauddin Hospital in Karachi from January 2025 to May 2025. Participants were selected through convenience sampling and 100 pregnant women agreed to participate in the study. Socio-demographic details were also gathered. The correlation between body image dissatisfaction and depression was tested using Spearman’s correlation coefficient. Results: Body image dissatisfaction have a significantly moderate negative relation with depression, with a coefficient of determination of -0.62 and a p-value of 0.001. A correlation was observed between body image satisfaction and depressive symptoms, with women with lower levels of body image satisfaction being higher in depressive symptoms. Conclusion: Depression in pregnant women is associated with body image perception. Addressing body image concerns may contribute to improved maternal mental health.